The Positivity Rate of IA-2A and ZnT8A in the Chinese Han Population With Type 1 Diabetes Mellitus: Association With rs1143627 and rs1143643 Polymorphisms in the IL1B Gene - Li, Jiaqi; Sun, Xiaoxiao; Luo, Shuoming; Lin, Jian; Xiao, Yang; Yu, Haibo; Huang, Gan; Li, Xia; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Pharmacology, 2021)
Objective: To investigate the association between susceptibility to type 1 diabetes mellitus (T1DM) and polymorphisms (rs1143627 and rs1143643) in the interleukin 1 beta (IL1B) gene in the Chinese Han population. Methods: The Meso Scale Discovery (MSD) method was used to detect the concentration of IL-1β in 24 T1DM patients and 27 healthy controls. MassARRAY was used to analyze the polymorphisms in the IL1B gene in 510 patients with classic T1DM and 531 healthy controls. The general data of the T1DM patients and healthy controls were compared by the chi-square test and Mann-Whitney U test. The chi-square test and logistic regression were used to analyze the frequency distributions of alleles and genotypes of polymorphisms in the IL1B gene. The Kruskal-Wallis H test and chi-square test were used for the genotype-phenotype analysis of rs1143627 and rs1143643 in the IL1B gene. Results: ① The concentration of IL-1β in T1DM patients was significantly higher than that in healthy controls. ② rs1143627 and rs1143643 in the IL1B gene were significantly correlated with the positivity rates for IA-2A and ZnT8A; genotype GG at rs1143627 and genotype CC at rs1143643 in the case group showed lower positivity rates for IA-2A and ZnT8A. ③ There was no significant difference in the genotypes or allele frequencies at rs1143627 (GG/GA/AA) or rs1143643 (CC/CT/TT) between the case group and control group (p > 0.05). ④ rs1143627 and rs1143643 were not found to be linked to T1DM susceptibility under different genetic models. Conclusion: rs1143627 and rs1143643 in the IL1B gene correlate with the positivity rate of IA-2A and ZnT8A in Chinese Han individuals with T1DM.